Adiposity and hyperleptinemia during the first trimester among pregnant women with preeclampsia - Yeboah FA; Ngala RA; Bawah AT; Asare-Anane H; Alidu H; Hamid AWM; Wumbee JDK (Dove Medical Press, 2017)
Francis Agyemang Yeboah,1 Robert Amadu Ngala,1 Ahmed Tijani Bawah,2 Henry Asare-Anane,3 Huseini Alidu,2 Abdul-Wahab Mawuko Hamid,2 Joshua Dokurugu Kwame Wumbee4 1Department of Molecular Medicine, Kwame Nkrumah University of Science and Technology, Kumasi, 2Department of Medical Laboratory Science, University of Health and Allied Sciences, Ho, 3Department of Chemical Pathology, School of Biomedical and Allied Health Sciences, University of Ghana, Accra, 4Internal Quality Control Unit, Quality Control Directorate, Kumasi Technical University, Kumasi, Ghana Background: Leptin levels start increasing from the early stages of pregnancy, irrespective of the maternal body mass index. Leptin levels are increased in pregnant women with preeclampsia (PE) and may precede the clinical onset of the disease, with peaks occurring around 28 weeks of gestation. This study was aimed at determining whether serum leptin concentration and body fat percentage are significantly altered during the first trimester in pregnancies that subsequently develop PE and whether such changes are useful in predicting the disease.Materials and methods: This was a prospective longitudinal study conducted among pregnant women in Ho municipality. A cohort of 314 pregnant women was monitored from the first antenatal visit to delivery period at the Volta Regional Hospital, Ho, Ghana. Maternal serum leptin and lipid profile were analyzed and body fat percentage determined during first trimester. Body mass index was also calculated.Results: First trimester serum leptin level (P<0.0001) and body fat percentage (P<0.0001) were significantly higher in those who developed PE than those who did not; while triglycerides (P=0.8600), total cholesterol (P=0.5620), high-density lipoprotein (P=0.5880), low-density lipoprotein (P=0.4870) and very low-density lipoprotein (P=0.6540) did not show any significant difference between those with PE and those without PE.Conclusion: Leptin levels are increased significantly during the first trimester of pregnancy in obese women with PE, and these increases precede the onset of PE. Keywords: bioelectrical impedance analysis, dyslpidemia, body mass index, hypertension